The use of paired reading method to teach reading skill for the eight grade students of Islamic boarding school - Ulvia Ramadhani Wahyuddin; Sahraini Sahraini; Andi Tenrisanna Syam (English Education Journal, 2022)
This quasi-experimental research aimed at identifying the effect of paired reading method on the reading skill achievement of the eighth-grade students in the Islamic boarding school of Nurut Tauhid 2020/2021. To collect the data, 12 students were chosen as the subjects of purposive sampling. They were given a pre-test, treatments for 12 times by using paired reading method, and a post-test. The result of this study shows that paired reading method has a positive effect on the reading skill of the students at the Islamic boarding school of Nurut Tauhid. The researcher suggests that using a paired reading method can be an alternative way to improve their reading skills gradually. This research hopefully would become a consideration for a language teacher in the current context to implement paired reading in teaching reading in their classroom teaching.